Prevalence of Isotretinoin Therapy in Adolescents and Young Adults With and Without Atopic Dermatitis: A Nationwide Prescription-based Population Study - Cathrine H. Mohn; Hege S. Blix; Anja Maria Brænd; Per Nafstad; Jon Anders Halvorsen (Medical Journals Sweden, 2023)
Although isotretinoin has anti-inflammatory and immunomodulatory properties, it can exacerbate atopic dermatitis. National estimates of the extent to which patients with atopic dermatitis are affected by severe acne and isotretinoin tolerability are lacking. The aim of this study is to investigate isotretinoin therapy in patients with atopic dermatitis and to compare the nationwide prevalence with individuals without atopic dermatitis. All Norwegian residents were followed for 17 years until age 20-22 years in 2020. Approximately 28% of patients with atopic dermatitis had been treated for acne, and 8% had received isotretinoin before age 23 years. In those over 17 years old, significantly more patients with atopic dermatitis were treated with isotretinoin than those without. At age 22 years, 2.21% (95% confidence interval 1.92-2.49) of patients with atopic dermatitis were treated with isotretinoin, compared with 1.55% (95% confidence interval 1.44-1.65) of those without, representing 42.8% (1.43; 95% confidence interval 1.24-1.65) higher use in patients with atopic dermatitis. Patients who received long-term treatment (probable severe atopic dermatitis) tolerated isotretinoin similarly to patients who received short-term treatment (probable mild atopic dermatitis). There was significantly higher use of topical corticosteroids during isotretinoin therapy in patients with atopic dermatitis. Conclusively, severe acne (isotretinoin therapy) was associated with atopic dermatitis at the population level in young adults.